Pharmacokinetics of cobicistat boosted‐elvitegravir administered in combination with rosuvastatin. (17th January 2014) - Custodio, Joseph M.; Wang, Hui; Hao, Jia; Lepist, Eve‐Irene; Ray, Adrian S.; Andrews, Jessica; Ling, Kah Hiing J.; Cheng, Andrew; Kearney, Brian P; Ramanathan, Srinivasan
Abstract Statins are commonly used medications by HIV‐1 patients. Elvitegravir/cobicistat/emtricitabine/tenofovir DF is a single tablet regimen for the treatment of HIV. The pharmacokinetic interaction between cobicistat‐boosted elvitegravir (EVG/co) and rosuvastatin was evaluated. Breast cancer resistance protein (BCRP) and organic anion transporting polypeptide (OATP) 1B1 and 1B3 inhibition were assessed in vitro. Healthy subjects (N = 12) received a single dose of rosuvastatin 10 mg alone and in combination with EVG/co. Intensive pharmacokinetic sampling was conducted and safety was assessed throughout the study. Rosuvastatin pharmacokinetic exposure parameters were evaluated using 90% confidence intervals (CI) of the geometric mean ratio (GMR) of the test (combination) versus reference (rosuvastatin alone) using equivalence boundaries of 70–143% for AUCinf and 70–175% for Cmax. Elvitegravir and cobicistat inhibited BCRP and OATP in vitro, emtricitabine and TDF did not. Clinically, study treatments were well tolerated, with adverse events generally mild. Upon coadministration, rosuvastatin plasma concentrations increased (Cmax 89% higher), while AUCinf changes were modest (38% higher) and clinically nonrelevant, potentially driven by moderate inhibition of intestinal efflux by BCRP, and/or hepatic uptake by OATPs by EVG/co. Elvitegravir and cobicistat pharmacokinetics were comparable to historical data. Rosuvastatin may be coadministered with EVG/COBI/FTC/TDF without dose adjustment.